Щодо змісту адміністративно-юрисдикційної діяльності правоохоронних органів - Шоптенко, С. С.; Shoptenko, S. S. (Юридичний науковий електронний журнал. - 2014. - № 4. - С. 167-170, 2014)
Досліджено зміст адміністративно-юрисдикційної діяльності. Визначено систему правоохоронних органів України. Проаналізовано адміністративно-юрисдикційні повноваження правоохоронних органів. Визначено поняття та особливості адміністративно-юрисдикційної діяльності правоохоронних органів.

The content of the administrative-jurisdictional activity has been established. It has been established that the administrative and jurisdictional activity in law enforcement lies in investigating and resolving cases of administrative offenses, dealing with complaints against the actions or decisions of employees and resolving cases of disciplinary offenses. The system of law enforcement bodies of Ukraine has been defined. We researched legal acts that regulate administrative and jurisdictional activities of law enforcement agencies. We analyzed the administrative and jurisdictional powers of law enforcement agencies (on example of the prosecution, internal affairs and security services). We provided suggestions for improving the current legislation on administrative-jurisdictional activities of law enforcement bodies of Ukraine. The concept and features of the administrative-jurisdictional law enforcement have been defined. We defined the administrative-jurisdictional of law enforcement agencies as regulated by current legislation activities of law enforcement bodies in addressing and resolving of administrative disputes, carried out within their competence and in accordance with established procedures and forms.

Исследовано содержание административно-юрисдикционной деятельности. Определена система правоохранительных органов Украины. Проанализированы административно-юрисдикционные полномочия правоохранительных органов. Определено понятие и особенности административно-юрисдикционной деятельности правоохранительных органов.
Regarding to the content of the administrative-jurisdictional law enforcement agencies
Относительно содержания административно-юрисдикционной деятельности правоохранительных органов
Keywords: адміністративно-юрисдикційна діяльність; правоохоронні органи; провадження у справах про адміністративні правопорушення; скарга; дисциплінарне провадження; administrative and jurisdictional activity; law enforcement; proceedings on administrative violations; complaints; disciplinary proceedings; административно-юрисдикционная деятельность; правоохранительные органы; производство по делам об административных правонарушениях; жалоба; дисциплинарное производство